If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(2r + 5) = 0 Reorder the terms: x(5 + 2r) = 0 (5 * x + 2r * x) = 0 Reorder the terms: (2rx + 5x) = 0 (2rx + 5x) = 0 Solving 2rx + 5x = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-5x' to each side of the equation. 2rx + 5x + -5x = 0 + -5x Combine like terms: 5x + -5x = 0 2rx + 0 = 0 + -5x 2rx = 0 + -5x Remove the zero: 2rx = -5x Divide each side by '2x'. r = -2.5 Simplifying r = -2.5
| x(6.75-x^2)=2.7 | | (7x+4)(3x-5)=0 | | 6x^4+12x^3+12x= | | 0=3x^2-9x+6 | | (3x+22)(7x-26)=x | | -5x^4-2x+1=0 | | x^2+2x+1=2x^2-2x-20 | | 9x+18-8x=-3-12 | | 0=2x^2+4x-6 | | 8n^2-98=0 | | (3x-8)(5x+6)=0 | | 5x(6-7)7=13 | | 7(x-3)+3(4-3)=-8 | | [(1)(2)](3)=[(2)(1)](3) | | 0=(2x-4):(x+1) | | X+1(29)3x= | | y=1.5+1.5x | | n^2=-2n+8 | | 29*6= | | y=1.5+1.5y | | x+12=3x-18 | | 5(4x-2)+3=11 | | 0=X^2+8x+2 | | 9x-7/8=7 | | -20=-4k-6k | | -8y=-12-12x | | 9t-9=32-4t+24 | | 20tan^2x=3+9sec^2x | | Sec^2x=1+tan^2x | | 0=2x^2-8x+5 | | 2-x=3x+2 | | 3x+1=6-2x |